2000
DOI: 10.1097/00004872-200018040-00013
|View full text |Cite
|
Sign up to set email alerts
|

Headache in patients with mild to moderate hypertension is generally not associated with simultaneous blood pressure elevation

Abstract: Our results did not support the opinion that headache experienced by stage 1-2 hypertensives was generally caused by simultaneous elevation in blood pressure. The direct mechanisms of headache in hypertension, as well as the relation between increments in blood pressure above 180/110 mmHg and headache, need further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
1
27
3
3
Order By: Relevance
“…This is an observation that could not be made in previous analyses of other interventional trials, 14,[17][18][19][20][21][22][23][24][25][26][27] because only in ELSA ABP was systematically measured before treatment and repeatedly during several years of treatment, 29 whereas in most other studies ABP monitoring was limited to a relatively small subgroup of patients or done during treatment only. As to the effects of treatment on office BP, our data were derived from a controlled trial, with treatment steps determined by protocol according to the achieved DBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an observation that could not be made in previous analyses of other interventional trials, 14,[17][18][19][20][21][22][23][24][25][26][27] because only in ELSA ABP was systematically measured before treatment and repeatedly during several years of treatment, 29 whereas in most other studies ABP monitoring was limited to a relatively small subgroup of patients or done during treatment only. As to the effects of treatment on office BP, our data were derived from a controlled trial, with treatment steps determined by protocol according to the achieved DBP.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Furthermore, the effect of treatment on ABP values of WCH individuals is by no means clear because the reports range from a marked ABP fall to an ABP fall with some drugs only to no ABP fall at all. 14,[17][18][19][20][21][22][23][24][25][26][27] Previous studies on the BP effects of antihypertensive treatment in WCH have usually assessed ABP by just one 24-hour recording, sometimes without a baseline reference value.14,28 Primary aim of the present study has been to address the issue in a more adequate fashion by taking advantage of the unique data provided by the European Lacidipine Study on Atherosclerosis (ELSA) trial, 29 the only prospective antihypertensive treatment trial in which all patients with moderate elevations of both systolic BP (SBP) and diastolic BP (DBP) had office and ABP measured (1) before randomization to treatment and (2) at 6-month (office BP) and 12-month (ABP) intervals during treatment over a follow-up of 4 years. The multiple office and ABP measurements during the treatment period allowed us to more properly address also other issues relevant to WCH, such as the modification with time of the difference between office and ABP, often defined as the WC effect, 14,30 and the effect of treatment on within 24 hours and visit-to-visit BP variability (short-and long-term variability) of WCH vis-à-vis sustained hypertensive individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of any variation of blood pressure around episodes of headache strengthens the interpretation that there is no such association. 10,11 We cannot discard, also, a potential association between headache and blood pressure in patients with secondary hypertension. This possibility is also unlikely, since patients with such condition were just a small proportion of the whole sample.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] More recent studies, with ambulatory blood pressure monitoring, 10,11 have showed that blood pressure did not vary around episodes of headache in patients already suffering from hypertension. In a population-based study, we demonstrated that not only blood pressure was unrelated to the complaint of headache, but that individuals with migraine tended to have lower blood pressure than individuals without migraine.…”
Section: Introductionmentioning
confidence: 99%